2020
DOI: 10.1111/jocd.13480
|View full text |Cite
|
Sign up to set email alerts
|

650 usec 1064nm Nd:YAG laser treatment of acne: A double‐blind randomized control study

Abstract: BackgroundA variety of energy‐based devices have been used to treat acne. However, all studies have been subjective and have not involved double‐blind and randomized controlled studies.AimsWe undertook a randomized controlled study evaluating the use of a 650 usec 1064 nm Nd:YAG laser compared with a sham in the treatment of acne.Patients/MethodsA total of 20 subjects with moderate‐to‐severe acne were randomized to receive either 650 usec 1064nm Nd:YAG laser or sham treatment. All subjects received 3 treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Additional Nd:YAG laser technologies demonstrating benefit in acne include the 650-ms platform. In a doubleblinded, randomized controlled study, ten patients with moderate-to-severe acne underwent four treatments, and showed a 42% reduction in inflammatory lesion count and an 18% reduction in sebum production [51]. All measured parameters in the study were significantly better than the sham group.…”
Section: -Nm Neodymium:yttrium Aluminum Garnet (Nd:yag) Lasermentioning
confidence: 91%
“…Additional Nd:YAG laser technologies demonstrating benefit in acne include the 650-ms platform. In a doubleblinded, randomized controlled study, ten patients with moderate-to-severe acne underwent four treatments, and showed a 42% reduction in inflammatory lesion count and an 18% reduction in sebum production [51]. All measured parameters in the study were significantly better than the sham group.…”
Section: -Nm Neodymium:yttrium Aluminum Garnet (Nd:yag) Lasermentioning
confidence: 91%
“…The treatment is virtually painless due to the rapid pulse duration. Furthermore, its deep penetrating property helps decrease sebum production in acne, reduce inflammation, and prevent future occurrences [58,59].…”
Section: Laser Treatmentmentioning
confidence: 99%
“…A double‐blind randomized controlled study by Kesty and Goldberg 26 demonstrate the Aerolase Neo as compared to sham treatment (with the same laser and no energy emitted from the device) in the treatment of inflammatory AV. The study results included an IGA improvement of 271% improvement in the laser versus the sham device.…”
Section: Near‐infrared Lasers To Treat Av Lesionsmentioning
confidence: 99%